Functionally linked amygdala and prefrontal cortical regions are innervated by both single and double projecting cholinergic neurons - Barabás, Bence; Reéb, Zsófia; Papp, Orsolya I.; Hájos, Norbert (Frontiers in Cellular Neuroscience, 2024)
Cholinergic cells have been proposed to innervate simultaneously those cortical areas that are mutually interconnected with each other. To test this hypothesis, we investigated the cholinergic innervation of functionally linked amygdala and prefrontal cortical regions. First, using tracing experiments, we determined that cholinergic cells located in distinct basal forebrain (BF) areas projected to the different nuclei of the basolateral amygdala (BLA). Specifically, cholinergic cells in the ventral pallidum/substantia innominata (VP/SI) innervated the basal nucleus (BA), while the horizontal limb of the diagonal band of Broca (HDB) projected to its basomedial nucleus (BMA).In addition, cholinergic neurons in these two BF areas gave rise to overlapping innervation in the medial prefrontal cortex (mPFC), yet their axons segregated in the dorsal and ventral regions of the PFC. Using retrograde-anterograde viral tracing, we demonstrated that a portion of mPFCprojecting cholinergic neurons also innervated the BLA, especially the BA. By injecting retrograde tracers into the mPFC and BA, we found that 28% of retrogradely labeled cholinergic cells were double labeled, which typically located in the VP/SI. In addition, we found that vesicular glutamate transporter type 3 (VGLUT3)-expressing neurons within the VP/SI were also cholinergic and projected to the mPFC and BA, implicating that a part of the cholinergic afferents may release glutamate. In contrast, we uncovered that GABA is unlikely to be a co-transmitter molecule in HDB and VP/SI cholinergic neurons in adult mice. The dual innervation strategy, i.e., the existence of cholinergic cell populations with single as well as simultaneous projections to the BLA and mPFC, provides the possibility for both synchronous and independent control of the operation in these cortical areas, a structural arrangement that may maximize computational support for functionally linked regions. The presence of VGLUT3 in a portion of cholinergic afferents suggests more complex functional effects of cholinergic system in cortical structures.